2004
DOI: 10.1128/aem.70.8.4702-4710.2004
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a Heterologous Manganese Superoxide Dismutase Gene in Intestinal Lactobacilli Provides Protection against Hydrogen Peroxide Toxicity

Abstract: In living organisms, exposure to oxygen provokes oxidative stress. A widespread mechanism for protection against oxidative stress is provided by the antioxidant enzymes: superoxide dismutases (SODs) and hydroperoxidases. Generally, these enzymes are not present in Lactobacillus spp. In this study, we examined the potential advantages of providing a heterologous SOD to some of the intestinal lactobacilli. Thus, the gene encoding the manganese-containing SOD (sodA) was cloned from Streptococcus thermophilus AO54… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
69
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(72 citation statements)
references
References 58 publications
0
69
0
1
Order By: Relevance
“…Previous studies have shown that the endogenous SOD levels control the iron-dependent HO ⅐ formation when cells are exposed to hydrogen peroxide (13,14,42) or such formation is due to an iron overload as in the Fur mutant of E. coli (58 (3,13), likely by interfering with the generation of HO. Figure 5 is a schematic presentation showing how MnSOD, iron chelation, or hydroperoxidases could protect the cells from both organic acid (e.g., lactic acid) and ROS stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that the endogenous SOD levels control the iron-dependent HO ⅐ formation when cells are exposed to hydrogen peroxide (13,14,42) or such formation is due to an iron overload as in the Fur mutant of E. coli (58 (3,13), likely by interfering with the generation of HO. Figure 5 is a schematic presentation showing how MnSOD, iron chelation, or hydroperoxidases could protect the cells from both organic acid (e.g., lactic acid) and ROS stress.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has shown that S. thermophilus possesses only one type of SOD, the Mn-containing enzyme (MnSOD) (3,15,44). The gene encoding MnSOD (sodA) from S. thermophilus AO54 has been characterized, cloned, and heterologously expressed in other bacteria (3,13,14). Unlike most sodA genes, the S. thermophilus sodA gene is constitutively expressed and is not induced by oxygen or the redox cycling compound paraquat (15).…”
mentioning
confidence: 99%
“…bulgaricus and Streptococcus thermophilus from the Culture Collection of the Centro de Referencia para Lactobacilos (CERELA) (San Miguel de Tucumán, Argentina) diminished the severity of inflammation in a mouse model of chemically induced colitis by modulating the immune response of the host, mainly due to an increase in the number of interleukin-10 (IL-10)-producing cells at the intestinal level with a significant decrease of IL-17 and IL-12 production (5, 6). More recently, it has been described that genetically engineered lactic acid bacteria (LAB) producing antioxidant enzymes such as catalase (CAT) or superoxide dismutase (SOD) were able to reduce the inflammation in different murine models of chemically induced colitis through a different mechanism, which was a reduction of reactive oxygen species (ROS) levels in the gut (7)(8)(9)(10). From this perspective, we hypothesized that the expression of such antioxidant enzymes in LAB strains with proven intrinsic immunomodulatory properties could enhance their anti-inflammatory activities.…”
mentioning
confidence: 99%
“…Many in vitro studies, reported that LAB strains possess antioxidant properties and inactivate ROS via enzymatic mechanisms, e.g. by a coupled NADH oxidase/ peroxidase system, superoxide dismutase and catalase [58][59][60]. The yoghurt bacteria Lactobacillus delbrueckii and Streptococcus thermophilus inhibited peroxidation of lipids through scavenging the reactive oxygen radicals, such as hydroxyl radical, or hydrogen peroxide [61].…”
Section: Discussionmentioning
confidence: 99%